1999
DOI: 10.1046/j.1469-8137.1999.00442.x
|View full text |Cite
|
Sign up to set email alerts
|

Androdioecy in the entomophilous tree Fraxinus ornus (Oleaceae)

Abstract: Androdioecy (the coexistence of two genders, cosexuals and males, in a single population) is a rare breeding system. In terms of functional gamete production, androdioecy has been reported in a small number of windpollinated and insect-pollinated species. In this study we examine the floral biology, stability of gender, and fruit and seed production after self-pollination and outcrossing pollination in a potentially androdioecious tree, Fraxinus ornus, in southern France. Individual trees have either he… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

2
52
2
1

Year Published

2004
2004
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 49 publications
(57 citation statements)
references
References 32 publications
(44 reference statements)
2
52
2
1
Order By: Relevance
“…This is inconsistent with an interpretation of functional androdioecy, in which males must be the minority gender (see Pannell 2002b), and it strongly implicates cryptic dioecy, with hermaphrodites that are, in fact, functionally female (Charlesworth 1984;Mayer & Charlesworth 1991). However, studies of F. ornus (Dommée et al 1999, and this paper), and the related F. lanuginosa (Ishida & Hiura 1998) and Phillyrea angustifolia (Lepart & Dommée 1992;Traveset 1994;Vassiliadis et al 2000), have found that, although pollen produced by hermaphrodites is less able to fertilize ovules than that produced by males, hermaphrodites can, and do, sire seeds. Indeed, in a paternity analysis within a small population of P. angustifolia, Vassiliadis et al (2002) recently showed that hermaphrodites actually sired as many seeds as did males under natural pollination conditions.…”
Section: Introductioncontrasting
confidence: 39%
See 1 more Smart Citation
“…This is inconsistent with an interpretation of functional androdioecy, in which males must be the minority gender (see Pannell 2002b), and it strongly implicates cryptic dioecy, with hermaphrodites that are, in fact, functionally female (Charlesworth 1984;Mayer & Charlesworth 1991). However, studies of F. ornus (Dommée et al 1999, and this paper), and the related F. lanuginosa (Ishida & Hiura 1998) and Phillyrea angustifolia (Lepart & Dommée 1992;Traveset 1994;Vassiliadis et al 2000), have found that, although pollen produced by hermaphrodites is less able to fertilize ovules than that produced by males, hermaphrodites can, and do, sire seeds. Indeed, in a paternity analysis within a small population of P. angustifolia, Vassiliadis et al (2002) recently showed that hermaphrodites actually sired as many seeds as did males under natural pollination conditions.…”
Section: Introductioncontrasting
confidence: 39%
“…Fraxinus ornus is one of the very few plant and animal species in which males co-occur with hermaphrodites (androdioecy) (Dommée et al 1999;Verdú 2004). The species is particularly interesting because it belongs to a family, the Oleaceae, in which androdioecy has putatively evolved from hermaphroditism several times independently (Wallander 2001;Pannell 2002a).…”
Section: Introductionmentioning
confidence: 99%
“…The species has previously been described as androdioecious (Dommée et al 1999), but the fact that males typically occur at a frequency of 0.5 indicates that F. ornus is functionally dioecious and that hermaphrodites are thus func- tionally female (Verdú et al 2004, and see Discussion). If hermaphrodites do sire progeny in nature, either through selfing or outcrossing, or both, and if these progeny do not themselves contribute their genes to subsequent generations (as the sex ratios suggest), then any siring performed by hermaphrodites would represent a cost of outcrossing that is exactly analogous to the cost of ovule discounting through self-fertilization and inbreeding depression.…”
mentioning
confidence: 99%
“…Fraxinus ornus (Oleaceae) is an insect-pollinated tree in which males cooccur with individuals that produce both seeds and pollen (Dommée et al 1999;Verdú 2004;Verdú et al 2004). The species has previously been described as androdioecious (Dommée et al 1999), but the fact that males typically occur at a frequency of 0.5 indicates that F. ornus is functionally dioecious and that hermaphrodites are thus func- tionally female (Verdú et al 2004, and see Discussion).…”
mentioning
confidence: 99%
“…Previously known only in a few plants (1)(2)(3)(4)(5)(6)(7)(8)(9)(10) and invertebrate animals (11)(12)(13)(14)(15), androdioecy has also evolved independently in a vertebrate species: the mangrove killifish, Kryptolebias (formerly Rivulus) marmoratus. Most surveyed populations of K. marmoratus consist primarily or exclusively of hermaphroditic individuals, but gonochoristic males are observed occasionally, and recent genetic evidence suggests that such individuals may mediate infrequent outcross events in this otherwise self-fertilizing species (16)(17)(18).…”
mentioning
confidence: 99%